SUPLEMEN EKSTRAK DAUN SIRIH, Piper betle, Lin DALAM MENURUNKAN KADAR MALONDIALDEHID PADA TIKUS WISTAR - Suirta, I W.; Asih, I. A. R. A. (Jurnal Kimia (Journal of Chemistry), 2019)
Betel leaf extract supplements, Piper betle Lin , was made by extracting maceration of betel leaves with ethanol 96%. Phytochemical screening of betle leaf extract obtained secondary metabolites such as : terpenoids, steroids, phenolics, and saponins . The results of the antioxidant activity test test showed that n-hexane fraction was more reactive as an antioxidant (IC 50 26,73 mg/L)  than the diethyl ether fraction (IC 50 114,54 mg/L). The MDA analysis showed that the betel leaves have a very good ability to reduce MDA levels. The concentration of MDA with addition of allopurinol (as positive control) was 0,41±0,0021?L/mL, while with addition of betel leaves the level was 0,44±0,0021?L/mL. The structure identification obtained active antioxidant compounds such as: cavicol, eugenol, caryophilene and isoeugenol. Keywords : betel leaf, malondialdehyde, Piper betle, wistar rat